Effects of whole-body electromyostimulation associated with dynamic exercise on functional capacity and heart rate variability after bariatric surgery: a randomized, double-blind and sham-controlled trial - Ricci, Paula Angélica (2020)
Purpose: Bariatric surgery is the most effective treatment for morbid obesity. In association with dietary restrictions, the ability to exercise in the immediate post-surgical phase is limited. In this context, whole-body electromyostimulation (WB-EMS), strategy that stimulates various muscle groups, in conjunction with physical exercise, holds promise for improving functional capacity, and cardiac autonomic control, following surgery. The purpose of this study was to analyze whether a rehabilitation program consisting of WB-EMS with 30 exercise training sessions following bariatric surgery significantly improves functional capacity, body mass and heart rate variability (HRV). Methods: Randomized, double-blind, and sham-controlled trial. Twenty obesity patients were randomized into the WB-EMS (n = 10) and sham (n = 10) groups. On average, 7 days after surgery, individuals underwent a six-minute walk test (6MWT), HRV, and body composition analysis at rest. The next day, patients initiated an exercise training protocol, five times per week, over 6 weeks. Walking distance changes (post-pre = ΔWD) obtained by 6MWT and HRV indices were determined following the intervention. Results: Only WB-EMSG significantly increased WD and body mass index (BMI) after the intervention (p = 0.002) and ΔWD was significantly higher in this group when compared with sham (p = 0.04). Moreover, both groups demonstrated an improvement in key measures of HRV after the intervention. Conclusion: An exercise training intervention initiated shortly after bariatric surgery improved functional capacity and cardiac autonomic tone. Improvements in functional capacity and BMI following exercise training were greater with the addition of WB-EMS but did not promote additional improvements in HRV beyond that realized with exercise training alone.